Pathogenic Variants in CEP85L Cause Sporadic and Familial Posterior Predominant Lissencephaly - Tsai, Meng Han; Muir, Alison M.; Wang, Won nJing; Kang, Yi Ning; Yang, Kun Chuan; Chao, Nian Hsin; Wu, Mei Feng; Chang, Ying Chao; Porter, Brenda E.; Jansen, Laura A.; Sebire, Guillaume; Deconinck, Nicolas; et al. (Elsevier, 2020)
Lissencephaly (LIS), denoting a “smooth brain,” is characterized by the absence of normal cerebral convolutions with abnormalities of cortical thickness. Pathogenic variants in over 20 genes are associated with LIS. The majority of posterior predominant LIS is caused by pathogenic variants in LIS1 (also known as PAFAH1B1), although a significant fraction remains without a known genetic etiology. We now implicate CEP85L as an important cause of posterior predominant LIS, identifying 13 individuals with rare, heterozygous CEP85L variants, including 2 families with autosomal dominant inheritance. We show that CEP85L is a centrosome protein localizing to the pericentriolar material, and knockdown of Cep85l causes a neuronal migration defect in mice. LIS1 also localizes to the centrosome, suggesting that this organelle is key to the mechanism of posterior predominant LIS. © 2020 Elsevier Inc.